Reaction-induced porosity fingering: Replacement dynamic and porosity evolution in the KBr-KCl system. (1st July 2018) - Beaudoin, Nicolas; Hamilton, Andrea; Koehn, Daniel; Shipton, Zoe Kai; Kelka, Ulrich
Abstract: In this contribution, we use X-ray computed micro-tomography (X-CT) to observe and quantify dynamic pattern and porosity formation in a fluid-mediated replacement reaction. The evolution of connected porosity distribution helps to understand how fluid can migrate through a transforming rock, for example during dolomitization, a phenomenon extensively reported in sedimentary basins. Two types of experiment were carried out, in both cases a single crystal of KBr was immersed in a static bath of saturated aqueous KCl at room temperature and atmospheric pressure, and in both cases the replacement process was monitored in 3D using X-CT. In the first type of experiment a crystal of KBr was taken out, scanned, and returned to the solution in cycles (discontinuous replacement). In the second type of experiment, 3 samples of KBr were continuously reacted for 15, 55 min and 5.5 h respectively, with the latter being replaced completely (continuous replacement). X-CT of KBr-KCl replacement offers new insights into dynamic porosity development and transport mechanisms during replacement. As the reaction progresses the sample composition changes from KBr to KCl via a K(Br, Cl) solid solution series which generates porosity in the form of fingers that account for a final molar volume reduction of 13% when pure KCl is formed. These fingers form during an initial and transient advection regime followed by a diffusion dominated system, which is reflected by the reaction propagation, front morphology, and mass evolution. The porosity develops as fingers perpendicular to the sample walls, which allow a faster transport of reactant than in the rest of the crystal, before fingers coarsen and connect laterally. In the continuous experiment, finger coarsening has a dynamic behaviour consistent with fingering processes observed in nature. In the discontinuous experiment, which can be compared to rock weathering or to replacement driven by intermittent fluid contact, the pore structure changes from well-organized parallel fingers to a complex 3D connected network, shedding light on the alteration of reservoir properties during weathering.